A balancing act: IPRs and public agriculture research. (2nd December 2011) - Muraguri, Lois
International Agriculture Research Centres (IARCs) and other public research organisations increasingly find themselves exposed to intellectual property rights due to inter alia the advent of the intellectual property system, privatisation of research and increased collaboration with the private sector. There is an inherent theoretical conflict in the application of private rights for the provision of public goods given that intellectual property rights (IPRs) introduce excludability to a good. But there is a distinction between the existence and exercise of IPRs. The latter, conducted creatively, can mitigate the excludability effect brought about by the former. Examples of the creative exercise of IPRs illustrate that IP capacity is vital. IARCs and other public research organisations particularly those in developing countries must invest in IP capacity in order to formulate creative IP policies and strategies and implement them in a manner that ensures their public goods mandate is not compromised.